(untitled) (World Science, 2021)
The paper is aimed at assessing the impact of the initial presentation of genital prolapse (GP) on women’s life quality. Materials and Methods. The study involved 120 women with GP of grade 1-2, who were divided into two groups. The treatment group (90 patients) consisted of three subgroups: 1a (n = 30) – GP correction by platelet-rich autoplasma, 1b (n = 30) – GP treatment by hyaluronic acid-based agent (Neauvia Organic Intense Rose, Switzerland), 1c (n = 30) – GP treatment using laser system CO2 (SmartXideDOT, DEKA, Italy). The experimental group consisted of 30 patients who underwent GP correction by training the pelvic floor muscles individually according to the standard method. Results. The obtained results in studying the life quality of women, who underwent non-surgical correction of the initial stages of GP, show that the rate of limited daily physical activity in patients with GP before correction was poor in all study groups. Three months after the treatment, it improved in all 3 subgroups, with the most significant improvement in 1b and 1c subgroups in contrast to the experimental group, where this rate not only remained unchanged in the vast majority, but there was a deterioration and onset of new symptoms in some cases. Conclusions. The subjunctive assessment of the life quality of women and the dynamics of their complains before and after non-surgical correction of the initial stages of GP show a significant improvement in life quality as a result of treatment using the algorithm of differentiated approach depending on the type, stage, concomitant somatic pathology and morphological features of the vaginal wall.